Cameroon : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Cameroon. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Cameroon's economy has shown resilience in the face of the twin shocks of the oil price slump and heightened security threats, with the robust growth of 2014 continuing into 2015. Growth is broad-based and projected to reach 5.9 percent in 2015, buoyed by increased oil production and the performance of sectors benefiting from the ongoing public investment boom. Total revenue is projected to increase in 2015, owing to a strong performance in non-oil revenue. Growth is projected to moderate to 5.2 percent in 2016, as oil production stabilizes.